108k views
0 votes
Two ways to solve -2(4x+3)=12x-6

User Nissan
by
5.9k points

1 Answer

2 votes

Answer:


\huge\boxed{x=0}

Explanation:


-2(4x+3)=12x-6\qquad\text{divide both sides by (-2)}\\\\4x+3=-6x+3\qquad\text{subtract 3 from both sides}\\\\4x=-6x\qquad\text{add}\ 6x\ \text{to both sides}\\\\10x=0\qquad\text{divide both sides by 10}\\\\\boxed{x=0}\\\\=================================


-2(4x+3)=12x-6\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\(-2)(4x)+(-2)(3)=12x-6\\\\-8x-6=12x-6\qquad\text{add 6 to both sides}\\\\-8x=12x\qquad\text{subtract}\ 12x\ \text{from both sides}\\\\-20x=0\qquad\text{divide both sides by}\ (-20)\\\\\boxed{x=0}

User Nikita Madeev
by
5.6k points